Utilización de los concretos de alta resistencia y concretos celulares en la industria de la construcción ecuatoriana, clasificados por sectores: vivienda, electricidad, gas/petróleo, salud y educación - Cabrera, María Inés (2018)
In this paper the characteristics of conventional concrete and the specials concretes, mainly cellular andhigh strength are analyzed. The forms of production and their uses are valued, as well as the usability inEcuador on strategic sectors such as health, education, housing, gas / oil and electricity, from its mainmechanical properties. The excellent properties of the studied special concrete (cellular and high strength) were tested and the potential use of cellular concrete in the sectors of health, education and housing, where installations require less demanding mechanical properties than the electricity and gas / oil sectors, which requires in their facilities the use of high-strength concrete, with values of compressive strength greater than 700 kg/cm2.